The iron storm - Cussler, Clive; Du Brul, Jack B. (Cussler, Clive. Isaac Bell novels., 2025)
Detective Isaac Bell faces the horrors of the Great War while battling a mysterious anarchist group intent on bringing brutality to the shores of America in the next thrilling adventure in this #1 New York Times bestselling series from Clive Cussler. Van Dorn agent Isaac Bell knows that when the President of the United States asks you to undertake a special mission, the only appropriate answer is, "Right away, sir." As an official observer, Bell is supposed to avoid action, but that's like asking a fish to shun water. After battling in the trenches, he finds himself flying beside a group of Allied aviators, unwilling to let them fight alone, even when they are faced with capture. Bell and his compatriots are imprisoned in a medieval castle--one that's withstood the test of time and countless assaults by conventional weapons in its history. Escape lies tantalizingly close... but only with the help of the latest in battlefield technology. But freedom may be short-lived. Even in the middle of a World War, Bell finds there are forces worse than those arrayed against the Americans on the battlefield. Opponents who are so evil that they are willing to set aside whatever rules of war still exist to take the fight to where they think it belongs: the streets of the United States. And there's only one man who can stop them... Isaac Bell.